Characterization of Photocurable Functionalized-CNT Nanocoating to Mitigate the Naturally Emission of Radon Gas - Aziz, Aisha Dalila Ab; Harun, Mohd Hamzah; Zaharuddin, Izzuddin Mohamad; Ezani, Nor Adnin Ezani Mohd; Othman, Norfazlinayati; Mohamed, Mahathir; Alias, Mohd Sofian; Rahman, Mohd Faizal Abd; Umar, Khairil Nor Kamal; Mudri, Nurul Huda; Halim, Khairul Azhar Abdul; Mustafa, Mohamad Syahiran; Mejus, Lakam; Razalim, Faizal Azrin Abdul; Ismail, Rosley Che; Sani, Abdul Muiz Mohd; Faisal, Sharilla Mohd; Tajau, Rida (Balai Publikasi Indonesia, 2025)
This study focuses on the synthesis and characterization of an anti-radon photocurable nanocoating formulated using a UV-curable formulation incorporated with functionalized carbon nanotubes (F-CNTs). The coating was prepared using Ebecryl 600 (urethane acrylate oligomer) and TMPTA (monomer), with GPTMS as a coupling agent and various photoinitiator combinations. Different F-CNT loadings ranging from 0.1 to 0.9 wt% were studied to evaluate their effects on coating performance. The samples were cured under UV irradiation for 2–20 passes to investigate the influence of exposure time on polymer crosslinking. Characterization analyses including pendulum hardness, Fourier-transform infrared spectroscopy (FTIR), viscosity, gel content, and radon gas permeability were performed. Results indicated that the incorporation of F-CNTs enhanced the mechanical strength and crosslinking density of the coating. The optimal formulation exhibited a hardness of 150.33 s (BAPO + 8 passes) and a gel content of 97%. Furthermore, radon concentration measurements showed a 28.9% reduction after applying a single coating layer, confirming the coating’s potential as an effective barrier for radon gas mitigation.